Pelatihan Aplikasi Pembelajaran Online Sebagai Inovasi Pembelajaran Di SMK Hadziqiyyah Nalumsari Jepara - Wijayanti, Esti; Meimaharani, Rizkysari (Universitas Multi Data Palembang, Fakultas Ilmu Komputer dan Rekayasa, 2021)
One of the districts far from the city of Jepara is nalumsarithe existence of vocational high schools. In March 2020 thecoronavirus that attacked Indonesia until now still exists, the incomingoutbreak crippled the economy, sector tourism, also in the field ofeducation. In the field of education today is certainly a special concernby the government. Because education is the axis of the nation's future,the solution that is proposed to the government is distance learning(PJJ) or online. Online implemented in the education sector is notready to be implemented because there are many reasons. One of thestudents must have an android phone that must be installed whatsappbecause students are given tasks through whatsapp. Whatsapp users areconsidered less effective for learning methods.Solutions and external, for that online learning that uses the internet asa solution for educators to run learning activities that provideassistance to educators by using online learning applications.